The Need for Implementation Research for Community-based Interventions: Scientific Evidence Is Needed - Kathya Lorena Cordova-Pozo (Shiraz University of Medical Sciences, 2022)
As many countries cannot ensure sufficient or good quality of health, there are many community interventions around the world.